An initial evaluation of expanded hemodialysis on hospitalizations, drug utilization, costs, and patient utility in Colombia. Issue 5 (31st January 2021) - Ariza, Juan G.; Walton, Surrey M.; Suarez, Adriana M.; Sanabria, Mauricio; Vesga, Jasmin I.
Abstract: To examine new evidence linking expanded hemodialysis (HDx) using a medium cut‐off (MCO) membrane with hospitalizations, hospital days, medication use, costs, and patient utility. This retrospective study utilized data from Renal Care Services medical records database in Colombia from 2017 to 2019. Clinics included had switched all patients from high flux hemodialysis (HD HF) to HDx and had at least a year of data on HD HF and HDx. Data included demographic characteristics, comorbidities, years on dialysis, hospitalizations, medication use, and quality of life measured by the 36 item and Short Form versions of the Kidney Disease Quality of Life survey at the start of HDx, and 1 year after HDx, which were mapped to EQ‐5D utilities. Generalized linear models were run on the outcomes of interest with an indicator for being on HDx. Annual cost estimates were also constructed. The study included 81 patients. HDx was significantly associated with lower dosing of erythropoietin stimulating agents, iron, hypertension medications, and insulin. HDx was also significantly associated with lower hospital days per year (5.94 on HD vs. 4.41 on HDx) although not with the number of hospitalizations. Estimates of annual hospitalization costs were 23.9% lower using HDx and patient utilities did not appear to decline. HDx was statistically significantly associated with reduced hospitalization days and lower medication dosages. Furthermore, this preliminary analysis suggested potential for HDx being a dominant strategy in terms of costs and utility and should motivate future work with larger samples and better controls.